Ultrasound versus Clinical Examination to Estimate Fetal Weight at Term - Lanowski, Jan-Simon; Lanowski, Gabriele; Schippert, Cordula; Drinkut, Kristina; Hillemanns, Peter; Staboulidou, Ismini (Geburtshilfe und Frauenheilkunde, 2017)
Introduction At term, fetal weight estimation is an important factor for decisions about the delivery mode and the timing of labor induction. This study aimed to compare the accuracy of abdominal palpation with that of ultrasound performed by different examiners to estimate fetal weight. The study investigated whether differences in the examinersʼ training affected fetal weight estimates. The accuracy of the weight estimates made for fetuses with extreme birth weights was also evaluated. Finally, the accuracy of Johnsonʼs method and of Insler and Bernsteinʼs formula for estimating fetal weight were compared with the other two methods. Methods This prospective study included singleton pregnancies between 37 weeks of gestation and 12 days post-term planned for vaginal delivery or cesarean section. Ultrasound and abdominal palpation using Leopoldʼs maneuvers were performed by examiners with different levels of professional experience. Fetal weight was additionally estimated using Insler and Bernsteinʼs formula and Johnsonʼs method. Statistical analysis calculated the accuracy of fetal weight estimates for the different examiners and the four methods. Results A total of 204 women were included in the analysis. Trained ultrasound examiners were most accurate when estimating fetal weight compared with all other examiners. The comparison of all four methods showed that fetal weight was assessed most accurately with ultrasound. No learning curve could be established. BMI and advanced gestational age affected the accuracy of the estimated weight. The analysis showed that a greater deviation between estimated weight and actual weight occurred with all four methods for fetuses at either end of the extremes of fetal weight, i.e., with very low or very high birth weights. Conclusion Fetal weight should be estimated using ultrasound. A good ultrasound training is essential.
Keywords: fetal weight estimation; ultrasound; clinical examination